2014
DOI: 10.2136/vzj2013.10.0184
|View full text |Cite
|
Sign up to set email alerts
|

A Screening Tool for Delineating Subregions of Steady Recharge within Groundwater Models

Abstract: We have developed a screening method for simplifying groundwater models by delineating areas within the domain that can be represented using steady‐state groundwater recharge. The screening method is based on an analytical solution for the damping of sinusoidal infiltration variations in homogeneous soils in the vadose zone. The damping depth is defined as the depth at which the flux variation damps to 5% of the variation at the land surface. Groundwater recharge may be considered steady where the damping dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(86 citation statements)
references
References 64 publications
4
81
0
1
Order By: Relevance
“…The higher‐frequency events identified in the precipitation spectrum are not present in the groundwater spectrum suggesting that these precipitation events have less effect on groundwater levels. This is consistent with the findings of several studies [ Dickinson et al ., ; Velasco et al ., ] which showed that low‐frequency signals tend to be better preserved in the groundwater level record than high‐frequency signals because of damping in the unsaturated zone which is related to soil texture, depth to water, and mean and period of the infiltration flux. This also implies that the quasi‐decadal groundwater recharge events are highly important in supplying large amounts of recharge to the groundwater system.…”
Section: Resultsmentioning
confidence: 99%
“…The higher‐frequency events identified in the precipitation spectrum are not present in the groundwater spectrum suggesting that these precipitation events have less effect on groundwater levels. This is consistent with the findings of several studies [ Dickinson et al ., ; Velasco et al ., ] which showed that low‐frequency signals tend to be better preserved in the groundwater level record than high‐frequency signals because of damping in the unsaturated zone which is related to soil texture, depth to water, and mean and period of the infiltration flux. This also implies that the quasi‐decadal groundwater recharge events are highly important in supplying large amounts of recharge to the groundwater system.…”
Section: Resultsmentioning
confidence: 99%
“…The largest number of HYDRUS papers in VZJ simulated subsurface water fluxes and groundwater recharge (e.g., Dickinson et al, 2014; Pfletschinger et al, 2014; Rieckh et al, 2014; Turkeltaub et al, 2014; Fan et al, 2015; and Guber et al, 2015). Of these, Guber et al (2015) used HYDRUS‐2D to evaluate a new subsurface water retention technology consisting of subsurface polyethylene membranes installed within the soil profile to improve root‐zone water storage and to limit downward recharge fluxes.…”
Section: Selected Hydrus Applicationsmentioning
confidence: 99%
“…Fan et al (2015) used both HYDRUS‐1D and HYDRUS (2D/3D) to model the effects of plant canopy and roots on soil moisture and deep drainage in forested ecosystems. Dickinson et al (2014) used HYDRUS‐1D to verify the appropriateness of a proposed screening tool for delineating areas with constant groundwater recharge. Turkeltaub et al (2014) used data collected with a deep vadose zone monitoring system to calibrate HYDRUS‐1D and subsequently used the software to investigate the temporal characteristics of groundwater recharge and how recharge may be affected by climate change.…”
Section: Selected Hydrus Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] and [17]. The period of the forcings may be representative of irrigation cycles or seasonal or annual climatic variability identified through time series analysis of atmospheric or hydrologic data (e.g., Hanson et al, 2004; Gurdak et al, 2007; Dickinson et al, 2014; Velasco et al, 2017). The fine soil is a silty clay and the coarse soil is a sandy loam, which have differing soil hydrologic parameters (Table 1) that produce complex flow and water content responses at the layer boundary.…”
Section: Filtering Of Surface Forcings With Depth In Layered Soilmentioning
confidence: 99%